An unusual case of osteonecrosis of the jaw associated with dengue fever and periodontitis. (26th February 2016) - Indurkar, MS; Sethi, R
Abstract: Osteonecrosis is a disorder rarely occurring in the jaw. Dengue fever is a common mosquito‐borne disease prevalent in many countries including India. The following report presents an interesting case of maxillary osteonecrosis in a middle aged male with a history of dengue infection. We also diagnosed symptoms of chronic periodontitis, which may have potentiated the necrosis. This case report will describe a novel clinical presentation and management of osteonecrosis of the jaw (ONJ) of unknown origin and a possible pathogenesis explaining the association of ONJ with dengue fever and periodontitis.